Assessment of New Measurements to Assess First Metatarsal Elevation in Hallux Rigidus Compared to Controls. Issue 3 (11th September 2017) - Jones, Mackenzie; Sanders, Austin; Cunha, Rachael Da; Cody, Elizabeth; Sofka, Carolyn; Nguyen, Joseph; Deland, Jonathan; Ellis, Scott
Category: Midfoot/Forefoot Introduction/Purpose: While Metatarsus Primus Elevatus (MPE) has been implicated in the development of hallux rigidus, previous studies have presented conflicting findings regarding the relationship between an elevated first metatarsal and arthritis. This may be due to the variety of definitions for MPE and the radiographic measurement techniques that are used to assess it. The aim of this study was to examine the reliability of new radiographic measurements that take into account the elevation of the first metatarsal in relation to the proximal phalanx, rather than in relation to the second metatarsal as previously described, to assess for MPE. In addition, we aimed to determine whether the elevation of the first metatarsal was significantly different in hallux rigidus patients than in a control population. Methods: A retrospective chart review was conducted from prospectively collected registry data at the investigators' institution to identify patients with hallux rigidus (n=65). A size matched control cohort of patients without evidence for first metatarsophalangeal (MTP) joint arthritis were identified (n=65). Patients with a previous history of foot surgery, rheumatoid arthritis, or hallux valgus were excluded. Five blinded raters of varying levels of training, including two research assistants, a senior orthopedic resident, a foot & ankle fellow, and an attending radiologist, evaluated seven radiographic measurements for their reliability in assessing for MPE in hallux rigidus and control groups. Four of the seven measurements were newly designed taking into account the relationship of the first MTP joint. Inter- and intrarater reliability were calculated using Intraclass Correlation Coefficients (ICC) and categorized by Landis and Koch reliability thresholds. The measurements between the hallux rigidus and control populations were compared using an independent t-test. Results: Six of the seven radiographic measurements were found to have substantial to almost perfect interrater reliability (ICC=0.800 to 0.953) between all levels of training, except for the Proximal Phalanx-First Metatarsal Angle which showed moderate reliability (ICC=0.527) (Table). Substantial to almost perfect intrarater reliability (ICC=0.710-0.980) was demonstrated by the research assistants. Six of the seven measurements taken by the attending radiologist demonstrated significant differences in first metatarsal elevation between the hallux rigidus and control populations with the hallux rigidus group showing increased elevation (p=0.000-0.020). Only the First Metatarsal Elevation Angle failed to show a significant difference between the populations (p=0.368). However, the First Metatarsal Elevation Angle measurements of the research assistant and the senior orthopedic resident did show a significant difference between the two populations (p<0.050). Conclusion: This study confirmed the reliability of seven radiographic measurements used to assess for MPE, including three previously established and four newly described measurements. Observers across all levels of training were able to demonstrate reliable measurements. In addition, the measurements were used to show that hallux rigidus patients are more likely to have an elevated first metatarsal compared to patients without radiographic evidence for first MTP arthritis. These measurements could be used in future work to examine how the presence of MPE relates to the etiology and progression of hallux rigidus, and how it affects the results of operative treatment.